THE EFFECTIVENESS OF USING INFOGRAPHICS MEDIA TOWARDS STUDENTS READING COMPREHENSION AT SMK NU PACE NGANJUK - Anisya Dhiyak Laili; Caltira Rosiana (Journal of English Language Education, 2026)
This study aims to examine the effectiveness of using infographics towards reading comprehension of grade XI AK students at SMK NU Pace. The questionnaire results show that many grade XI AK students still experience difficulties in understanding reading texts. Infographic media was selected as a more interactive and visually based learning tool. This study used a quantitative method with a pre-experimental one-group pre-test and post-test design. The research subjects consisted of 38 eleventh-grade AK students at SMK NU Pace. Data were analyzed using descriptive and inferential analysis techniques. The results showed that the average reading comprehension of students before the implementation of infographic media was 63.95 with a standard deviation of 13.664, while after implementation, it increased to 74.47 with a standard deviation of 13.090. The statistical test using a paired sample t-test obtained a significance value of 0.001 (< 0.05), which means that there is a significant difference between the pre-test and post-test results. Based on these findings, it can be concluded that the use of infographic media is proven to be effective in improving students' reading comprehension.